Interaction of the European genotype porcine reproductive and respiratory syndrome virus (PRRSV) with sialoadhesin (CD169/Siglec-1) inhibits alveolar macrophage phagocytosis - De Baere Miet I; Van Gorp Hanne; Delputte Peter L; Nauwynck Hans J (Veterinary Research, 2012)
Abstract Porcine reproductive and respiratory syndrome virus (PRRSV) is an arterivirus that shows a restricted in vivo tropism for subsets of porcine macrophages, with alveolar macrophages being major target cells. The virus is associated with respiratory problems in pigs of all ages and is commonly isolated on farms with porcine respiratory disease complex (PRDC). Due to virus-induced macrophage death early in infection, PRRSV hampers the innate defence against pathogens in the lungs. In addition, the virus might also directly affect the antimicrobial functions of macrophages. This study examined whether interaction of European genotype PRRSV with primary alveolar macrophages (PAM) affects their phagocytic capacity. Inoculation of macrophages with both subtype I PRRSV (LV) and subtype III PRRSV (Lena) showed that the virus inhibits PAM phagocytosis. Similar results were obtained using inactivated PRRSV (LV), showing that initial interaction of the virion with the cell is sufficient to reduce phagocytosis, and that no productive infection is required. When macrophages were incubated with sialoadhesin- (Sn) or CD163-specific antibodies, two entry mediators of the virus, only Sn-specific antibodies downregulated the phagocytic capacity of PAM, indicating that interaction with Sn, but not CD163, mediates the inhibitory effect of PRRSV on phagocytosis. In conclusion, this study shows that European genotype PRRSV inhibits PAM phagocytosis in vitro, through the interaction with its internalization receptor Sn. If similar events occur in vivo, this interaction may be important in the development of PRDC, as often seen in the field.